Her name is Knight - Angoe, Yasmin (Nena Knight, 2021)
"Stolen from her Ghanaian village as a child, Nena Knight has plenty of motives to kill. Now an elite assassin for a powerful business syndicate called the Tribe, she gets plenty of chances. But while on assignment in Miami, Nena ends up saving a life, not taking one. She emerges from the experience a changed woman, finally hopeful for a life beyond rage and revenge. Tasked with killing a man she's come to respect, Nena struggles to reconcile her loyalty to the Tribe with her new purpose. Meanwhile, she learns a new Tribe council member is the same man who razed her village, murdered her family, and sold her into captivity. Nena can't resist the temptation of vengeance--and she doesn't want to. Before she can reclaim her life, she must leverage everything she was and everything she is to take him down and end the cycle of bloodshed for good."--